The Ultimate Bearing Capacity analysis of masonry arch bridges - Kefan Chen; Yuan Li; Qixiang Hui; Bin Zhou; Kang Wang (Građevinar)
To accurately evaluate the ultimate bearing capacity of masonry arch structures, considering the friction and bonding relationships between different components, a finite element model was established in this study with cohesive zero-thickness elements. The model was analysed using explicit dynamic simulations and verified through a case study. The results indicate that the thickness of the arch backfill and ring has a quadratic positive correlation with the ultimate bearing capacity of the structure, whereas the rise-span ratio has a cubic relationship. In particular, there is an optimal rise-span ratio (f/l = 1/3.909) to increase the bearing capacity of the structure under the same conditions.